(untitled) (Indian Journal of Child Health, 2019)
Introduction: Hypoglycemia is a common but preventable metabolic abnormality in neonates associated with long-term sequelae. Controversies still exist about its definition, screening methodology, management, and outcome making it a subject for further exploration. Objectives: The study was taken up to find out the proportion of neonate developing hypoglycemia in the neonatal intensive care unit (NICU) and to study the clinical profile of hypoglycemia in neonates. Materials and Methods: All intramural and extramural neonates admitted in the NICU within 2 h of delivery were included in this study. They were screened for hypoglycemia using Accutrend-alpha glucometer. Results along with all neonatal and maternal variables were recorded and analyzed using the SPSS version 15.0. Results: The current study shows the prevalence of hypoglycemia as 32.2%. Proportion of hypoglycemia was more in small for gestational age, large for gestational age neonates, and neonates with prematurity, birth asphyxia, and maternal diabetes mellitus. Besides, hypoglycemia occurred more commonly within 24 h of life. Lethargy, convulsion, apnea, and jitteriness were common presenting symptom. Conclusion: The present study shows despite advances in obstetrical practices and increase in institutional deliveries over years, neonatal hypoglycemia continues to occur with almost same frequency along with the same maternal and neonatal variables.